Linguocultural analysis of English and Uzbek proverbs - Uktamova Mohigul Khamidullo kizi (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
Proverbs and sayings are a significant piece of the practice of human language, since they are consecrated fortunes of individuals’ way of life and language, just as age-old information and abilities. Truly, the article’s fundamental point is to interpret English and Uzbek proverbs, which can masterfully address an assortment of features of life, social experience, and standpoint, mental, moral, and tasteful standards, just as the inventiveness of imaginative perspectives and inclinations. In addition, this research considers the methodological and analytical value of employing proverbs in English schools (that is to classify English proverbs in relation to the Uzbek equivalents, to consider the difficulties of translation from English proverbs into Uzbek language, and to conduct a comparative description of translation of English proverbs in Uzbek).